Red brick dorm lounge interior, 1963 (1963)
The lounge has a sofa, coffee table, end table, lamp, and large dresser. The coffee table and end table are constructed from a deeper wood, while the large dresser is made from a lighter wood. On the coffee table, there is a magazine and a dish.